Mechanical Behavior of Anisotropic Composite Materials as Micropolar Continua - Fantuzzi, Nicholas; Trovalusci, Patrizia; Dharasura, Snehith (Frontiers in Materials, 2019)
The macroscopic behavior of materials with anisotropic microstructure described as micropolar continua is studied in the present paper. Micropolar continua are characterized by more kinematical and dynamical descriptors than classical continua (Cauchy), as additional strain and stress fields, namely the micro-rotation and the relative rotation, and their work conjugated counterparts, the micro-couple and the skew-symmetric part of the stress, respectively. The presence of such enriched strain and stress fields can be mechanically observed especially when concentrated forces and geometric discontinuities are present. The effectiveness of the micropolar model to represent the behavior of materials made of particles of prominent size has been widely proved in the literature, in this paper we focus on the capability of this model to grossly capture the behavior of anisotropic solids under concentrated pressures. Numerical parametric analyses are performed for various classes of material symmetries using a finite element approach with quadratic elements.